New records of Rheumatobates Bergroth (Hemiptera: Heteroptera: Gerridae) from the Pacific coast of Colombia and Costa Rica, with a key to males of Rheumatobates in the Eastern Tropical Pacific - Padilla-Gil, Dora N.; Pacheco-Chaves, Bernald (Zootaxa, 2012)
Three species of the genus Rheumatobates, R. peculiaris, R. longisetosus, and R. probolicornis are recorded from the Pacific coast of Colombia, municipality of Tumaco (department of Nariño); and R. bergrothi is recorded from the Pacific coast of Costa Rica; the macropterous morph of R. longisetosus is described, ecological data are provided and it is included together with other four species in a key to adult males from Eastern Tropical Pacific; the male habitus for six species is illustrated.